Recent developments in the assessment of the immune response to malaria, especially as related to vaccination: Immunity to Plasmodium yoelii and Babesia microti: modulation by the CBA/N X-chromosome - Jayawardena, Anil N. (1979)
CBA/N mice carry an X-linked recessive defect expressed in cells of the B cell lineage. The major deficiency in these mice is an almost complete inability to respond to certain thymus-independent antigens, such as pneumococcal polysaccharide type III (S III). We have examined the responses of mice carrying the CBA/N X-chromosome to the malaria parasite Plasmodium yoelii and the piroplasm Babesia microti. We have found that the duration and severity of these infections is increased in mice carrying the CBA/N X-chromosome and that this is associated with a markedly defective IgM antibody response to the parasitized red cell and a failure to produce autoantibodies to bromelain-treated mouse RBCs. An autoimmune response directed at modified determinants on the red cell membrane may be one of the factors involved in the control of these infections.